Aplikasi Pencarian Rute dan Site BTS (Base Transceiver Station) Menggunakan Speech To Text pada Perangkat Android - Tiara Anggun Nur Fadhilah (Politeknik Negeri Malang, 2017)
In order to implement the technology development of a BTS (Base Transceiver Station) device from a project a vendor and operator. Take advantage of the services provided by the Android smartphone, namely Google maps along with voice, namely speech to text, can further help the performance of a survey team at the sub party contractor (subcon) / third part. The results of application testing and analysis show that speech to text testing for noise is: average for distances of 10cm and 35cm with a noise level of 63 dB as much as 79% success, on average for distances of 10cm and 35cm with a noise level of 70 dB as much as 75% success, average for the distance 10cm and 35cm with a noise level of 75 dB for 72% success. Testing time when opening Maps from the text to maps results, it is found that the speed of male voice is faster, namely 1 minute 51 seconds and 1 minutes 68 seconds than women. Finally, testing the comparison of the distance between the application and the calculation through the Euclidean Distance formula, the average distance obtained in the application is 3.65345287 km and the calculation result with the Euclidean Distance formula is 3,67 km.